Stress and Coping of Parents with Children Seeking Treatment from a Tertiary Care Mental Health Institute - Lohar, Stuti Sharma; Baruah, Arunjyoti; Kollipara, Sandeep (Indian Journal of Psychiatric Nursing, 2023)
Abstract Background: Parenting a child with special needs puts very high demands making it difficult to cope, and parents perceive stress which often results in lack of experiencing the joy of parenting. The negative psychological effects of having a child with disability emerged in the result of many studies. Aims: The study aimed to assess the stress and coping of parents with children seeking treatment from a tertiary care mental health. Objectives: The study objectives were to assess the stress, ways of coping of parents seeking treatment from tertiary care mental institute. To find out the association of stress, ways of coping of parents with selected demographic variables and to determine the correlation between stress and coping of parents. Materials and Methods: A quantitative approach and descriptive research design were adopted for this study. A total of 100 parents of children seeking treatment from child and adolescent clinic of tertiary care mental health institute, Tezpur, Assam. Study subjects were selected using a purposive sampling technique. Socio-demographic pro forma, parental stress scale, and ways of coping (revised) were used for data collection after ethical clearance and written permission from concerned authorities. Results: In parental stress, the mean score for the participants was 45.72 ± 8.25. Regarding the way of coping frequently used by the participants, 36% of participants had used positive reappraisal coping followed by multiple (two or more). Coping measures were used by 25% of participants and planful problem-solving by 20% of participants. There was no significant association found between parental stress and selected sociodemographic variables. Results showed a significant association between gender and ways of coping used by the participants in the coping strategy of distancing (x2 = 3.910, P = 0.048), accepting responsibility (x2 = 4.254, P = 0.039), and positive reappraisal (x2 = 10.364, P = 0.001). The significant association was found between planful problem-solving coping strategy and educational level of participants (x2 = 8.046, P = 0.005), birth order of the child seeking treatment (x2 = 4.557, Fisher's exact test = 0.043). Furthermore, the coping strategy, positive reappraisal was found significantly associated with age (x2 = 7.658, P = 0.006), gender (x2 = 10.364, P = 0.001), and occupation ((x2 = 5.396, P = 0.020) of participants. The result showed that there was no significant correlation between parental stress and ways of coping of parents of children seeking treatment from the child and adolescent clinic of a tertiary care mental institute. Conclusion: Our findings help to appreciate the many coping mechanisms that parents employ while caring for their children who have mental illness as well as parental stress. Effective intervention programs can be designed to educate parents and assist them in managing their stress by understanding various coping mechanisms, and how they affect parental stress. In a nation with little resources, psychiatric nurses and mental health professionals can mobilize resources that are sensitive to cultural differences and address the issue associated with parental stress and coping.